Outside the Box Leadership pada SMP Negeri Buti, Merauke, Papua: Perspektif Guru - Werang, Basilius Redan; Agung, Anak Agung Gede; Jampel, I Nyoman; Sudjana, I Wayan (Kelola: Jurnal Manajemen Pendidikan, 2023)
Effective leadership is crucial for guiding schools towards their goals. While traditional leadership traits play a role, this study focuses on identifying the non-traditional qualities that characterize the principal of SMP Negeri Buti, Merauke, a model school in Southern Papua. Utilizing a quantitative survey with all 20 teachers, the research revealed that the principal's willingness to take risks, respect for colleagues, and openness to diverse perspectives are key factors in their success. The data were analyzed statistically by calculating the frequency and percentage of responses on each item of the questionnaire. The result of descriptive statistical analysis indicates that daring to take risks, respect for sub-ordinates, and being open to the diversity of thinking and acting are the main keys to the success of the school principal in bringing SMP Negeri Buti as a ‘model’ for all schools around Southern Papua in general and in Merauke district in particular.